Gender Identity and Future Thinking About Parenthood: A Qualitative Analysis of Focus Group Data With Transgender and Non-binary People in the United Kingdom - Tasker, Fiona; Gato, Jorge (Frontiers in Psychology, 2020)
The idea that people who are transgender or non-binary are not interested in becoming parents has been refuted by several studies. However, both medical unknowns and cisnormativity surround the process of becoming a parent for transgender or non-binary people, with little known about the psychosocial impact on the family formation dilemmas of transgender and non-binary adults. Employing Life Course Theory as our theoretical framework, three focus group interviews were conducted with eleven transgender or non-binary adults. Qualitative data analysis of focus group interview transcripts was conducted through Thematic Analysis. Four overarching interlinked themes were identified concerning the dilemmas perceived by the nine participants who contemplated future parenthood: (i) Balancing a desire for parenthood and desires for other life goals; (ii) Feeling that who I am doesn’t fit into the cisgender system of accessing fostering, adoption or fertility services; (iii) Experiencing the conjoined challenges of gender and fertility embodiment as I see them; (iv) Searching for a non-binary or gender appropriate self and the need for flexible future planning centered on reproductive capacity. Overall, thoughts about gender transition were often interwoven with parenthood plans and in a dialectical fashion the desire and intention to have, or not have, children was implicated in satisfaction with gender transition. The significance of these themes is discussed in relation to how hopes for parenthood could be realized without jeopardizing gender identity and the need for a future focused, flexible, and open-minded approach on the part of fertility and adoption services.